Aetiological factor for chronic suppurative otitis media: a retrospective study - Darad, Hardik; Sinha, Mohit (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2017)
Background: Otitis media (OM) refers to a group of complex infectious and inflammatory diseases affecting the middle ear. The present study was conducted to understand the various aetiological factors in chronic suppurative otitis media (CSOM) and also to take into possible hereditary factors. Methods: This retrospective study was conducted in 150 patients who had visited or were admitted at department of otorhinolaryngology and Head and Neck Surgery, Shree Sayaji General (SSG) Hospital, Vadodara, Gujarat. Detailed history regarding the illness was taken then clinical examination was carried out on the patient in a systemic manner, otoscopic examination, tuning fork test and pure tone audiometry was done. All the findings are noted in proforma. Means of both groups were compared by independent student t-test. Results: Most of the patients were in lower socioeconomic class (59.33) and lower middle class (40.67). Fifty out of the 150 chronic suppuurative Otitis Media patients, had a history of discharge for more than 10 years of duration. DNS and septal spur was found as positive finding in 49 patients of CSOM. X-ray of mastoid Schuller’s view was done in 87 patients, out of which 62 patients X-ray showed sclerosis of mastoid air cells, 16 cases showed partly pneumatization of mastoid air cells. Conclusions: Chronic otitis media is an important cause of morbidity in very large group of Indian population. Between 20-40 years of age septal pathology was main aetiological factor for CSOM.